«The House of Asterion» by Borges: Becoming-minor and Myth Deterritorialization - Rosario Pérez Bernal (2018)
The purpose of this communication is to define the mechanisms of I decentering and resignification of the Minotaur from Greek mythology in the Borgesian bestiary, through some categories of Deleuze and Guattari, as well as some intertextual tools, so as to inquire whether the borgesian animal is a reservoir of intensive vital positions that contribute to a better understanding of what is human.